Study On Indoor Particulate Matter (Pm2.5) In Hostel Rooms Of Universiti Sains Malaysia Engineering Campus - Anuar, Auji Aseela (Universiti Sains Malaysia, 2022)
Good indoor air quality influenced the health and comfortability of the occupants. A study was conducted to investigate the relationship between the indoor particulate matter with a diameter less than 2.5 micron (PM2.5), ambient temperature, relative humidity and wind speed. The objectives of the study were to determine the current concentration level of PM2.5, evaluate the influence of occupancy and human activity on PM2.5 concentration level and discover the association between parameters using Pearson correlation. Four hostel rooms in USM Engineering Campus were selected in this study. The pollutant contributors were from the human activities inside the designated rooms and the surrounding area. The monitoring sessions were divided into two periods: semester break (SB) and academic session (AS). The Met One E-sampler (ODRM) was used to collect 24-hour data continuously and the collected data was analysed using SPSS software and Microsoft Excel to achieve the objectives of the study. Hostel rooms A, B and C had higher PM2.5 concentration levels during the AS monitoring than the SB monitoring. On the contrary, room D showed greater PM2.5 concentration level during the SB monitoring than the AS monitoring. Room B can be considered as the most polluted room because the concentration level (mean hourly average 8.41 μg/m3) in the room was the highest. Indoor and outdoor human activities contributed to the changes of PM2.5 concentration level. The outdoor sources of PM2.5 such as dust from nearby house renovation also have been considered in this study. According to the Pearson correlations, the key meteorological parameter that influenced the PM2.5 concentrations was ambient temperature. The study discovered that human activity was the major contributor to the PM2.5 concentration level in the USM Engineering Campus hostel rooms.